Employee Performance Improvement: Motivation and Environment Based Concepts - Ine Yuliawati; Sindrawati Sindrawati; Muhammad Syukrullah Abdullah (Jurnal Ekonomi, 2023)
The purpose of this research is to analyze and test the important role of motivation and work environment in efforts to improve employee performance. The approach used was quantitative and the sample used was 34 employees from the UPT Parking Office of the Bandung City Transportation Service. The results of the study show that motivation plays an important role in improving employee performance. While the work environment does not play an important role in increasing employees. It is important for the UPT Parking Dinas Perhubungan Bandung City to further analyze the factors that can improve the performance of its employees.